The Application of DAQ-Middleware to the J-PARC E16 Experiment. Issue 8 (December 2015) - Hamada, E; Ikeno, M; Kawama, D; Morino, Y; Nakai, W; Obara, Y; Ozawa, K; Sendai, H; Takahashi, T N; Tanaka, M M; Yokkaichi, S
Abstract: DAQ-Middleware is a software framework for network-distributed data acquisition (DAQ) systems. We adopted the framework for the J-PARC E16 experiment, which requires a DAQ bandwidth of more than 660 MB/spill (two-second spill per six-second cycle). We developed a prototype for the DAQ software and confirmed that the prototype's total throughput satisfies the requirements of the experiment.